2015
DOI: 10.15252/emmm.201505677
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cause and functional impact of altered synaptic lipid signaling due to a prg‐1 gene SNP

Abstract: Loss of plasticity‐related gene 1 (PRG‐1), which regulates synaptic phospholipid signaling, leads to hyperexcitability via increased glutamate release altering excitation/inhibition (E/I) balance in cortical networks. A recently reported SNP in prg‐1 (R345T/mutPRG‐1) affects ~5 million European and US citizens in a monoallelic variant. Our studies show that this mutation leads to a loss‐of‐PRG‐1 function at the synapse due to its inability to control lysophosphatidic acid (LPA) levels via a cellular uptake mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 48 publications
(132 reference statements)
2
86
0
Order By: Relevance
“…Tomosyn2 controls acetyl choline release from cholinergic nerve terminals (Geerts et al., 2015) and acetylcholine (ACh) is known to induce persistent γ-oscillations in the hippocampus (Picciotto et al., 2012). LysoPLD/ATX encodes one of the major enzymes involved in synthesis of lysophospatidic acid (LPA), a molecule with a key signaling role controlling both excitatory and inhibitory synapse functions (García-Morales et al., 2015, Vogt et al., 2015). LPA has a critical role in the nervous system: knockout of LPA1 receptor causes anxiety (Santin et al., 2009), which also characterizes the Slm2 mouse, and LysoPLD/ATX is essential for brain development (Greenman et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Tomosyn2 controls acetyl choline release from cholinergic nerve terminals (Geerts et al., 2015) and acetylcholine (ACh) is known to induce persistent γ-oscillations in the hippocampus (Picciotto et al., 2012). LysoPLD/ATX encodes one of the major enzymes involved in synthesis of lysophospatidic acid (LPA), a molecule with a key signaling role controlling both excitatory and inhibitory synapse functions (García-Morales et al., 2015, Vogt et al., 2015). LPA has a critical role in the nervous system: knockout of LPA1 receptor causes anxiety (Santin et al., 2009), which also characterizes the Slm2 mouse, and LysoPLD/ATX is essential for brain development (Greenman et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Plasticity-related gene 1 (PRG-1) is a member of the integrin family, which acts as a co-factor with LPA in modulating glutamate neurotransmission. It has been shown that the post-synaptic deficiency of PGR-1 prohibits LPA from entering the post-synaptic membrane, thereby leading to the accumulation of LPA in the synaptic cleft (Vogt et al, 2016). Thus, an increased level of LPA in the synaptic gap has been shown to have two complementary mechanisms which result in increased glutamate concentration in the synaptic cleft.…”
Section: Lpa and Neuroplasticitymentioning
confidence: 99%
“…Bioactive lipid phosphates initiate receptor-directed signaling cascades and regulate fundamental cellular processes (Moolenaar et al, 2004). PRG-1, however, interacts with LPA in a manner different from classical LPPs (McDermott et al, 2006) by enabling transmembrane transport of LPA to intracellular compartments (Trimbuch et al, 2009;Vogt et al, 2016). PRG-1 is expressed at postsynaptic sites of principal neurons and acts in a non-cell-autonomous fashion by controlling LPA in the synaptic cleft, which in turn stimulates presynaptic LPA receptors resulting in an increased release probability of glutamate vesicles at excitatory synapses (Tokumitsu et al, 2010;Trimbuch et al, 2009;Vogt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PRG-1, however, interacts with LPA in a manner different from classical LPPs (McDermott et al, 2006) by enabling transmembrane transport of LPA to intracellular compartments (Trimbuch et al, 2009;Vogt et al, 2016). PRG-1 is expressed at postsynaptic sites of principal neurons and acts in a non-cell-autonomous fashion by controlling LPA in the synaptic cleft, which in turn stimulates presynaptic LPA receptors resulting in an increased release probability of glutamate vesicles at excitatory synapses (Tokumitsu et al, 2010;Trimbuch et al, 2009;Vogt et al, 2016). Previous studies have shown that various members of the PRG family play a role in regulating structural plasticity, including filopodia formation, neurite extension, and brain reorganization after lesion (Brauer et al, 2003;Broggini et al, 2010;Coiro et al, 2014;Peeva et al, 2006;Savaskan et al, 2004;Sigal et al, 2007;Velmans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation